THE EFFECT OF DOSAGE AND TIME OF NPK FERTILIZER APPLICATION ON THE GROWTH AND YIELD OF RICE (Oryza sativa L.) VARIETY IR-64: PENGARUH DOSIS DAN WAKTU PEMBERIAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL PADI (Oryza sativa L.) VARIETAS IR-64 - Afdhalul Hilza; Tasliati Djafar (ROCE : Jurnal Pertanian Terapan, 2026)
This study aims to determine the most effective dose and timing of NPK fertilizer application and to examine their interaction on the growth and yield of rice plants. The study was conducted in Gampong Lampreh, Ingin Jaya District, Aceh Besar Regency, using the IR-64 rice seed variety obtained from the Samahani Main Seed Center (BBI). The study was arranged using a 3 × 3 factorial Randomized Block Design (RBD) with three replications, yielding 27 experimental units. The first factor was the NPK fertilizer dose, while the second was the timing of fertilizer application: 0 and 10 days, 10 and 20 days, and 15 and 30 days after planting. The parameters observed included plant height, number of tillers, and dry grain weight per hectare. The results showed that NPK fertilizer application significantly affected plant height at 35 and 75 days after planting (DAP), and had a very significant effect at 55 DAP. The number of tillers was significantly affected at 35 days after planting, very significantly at 55 days after planting, but not significantly different at 75 days after planting. NPK fertilizer treatment did not significantly affect dry grain weight per hectare. The best dose was obtained at 50 g NPK per plot. There was a significant interaction between the dose and timing of fertilizer application on plant height at 75 days after planting and on the number of tillers at 55 days after planting. In contrast, other parameters did not show significant interactions.